Caracterização e tratamento do efluente de lavagem em empresa de reciclagem de plásticos para fins de reuso - Rodrigues, Elisangela Garcia Santos (2013)
In the steps of the process of plastics recycling, the washing process produces an effluent with high organic load that requires treatment for disposal. In order to evaluating the organic load physicochemical parameters were analyzed in order to establish the best form of treatment for the effluent reuse in a plastic recycler at the washing process. Sample collection was made in the washing tank at the end of the washing process at determined cycles around 12:00h. According to the obtained results the need arises for the treatment of effluent, both to frame it in the discard parameters established by the legislation of the national council of the environment (CONAMA), and to reuse it inside the recycler. As proposal was used for washing effluent treatment the coagulation/flocculation process, where was applied three types of coagulants (ferric chloride, aluminum sulfate and polychloride aluminum) at doses ranging from 5mg.L-1 of 65mg.L-1 and the Fenton oxidative process. For the effluent under study, it was concluded that the ferric chloride has a higher efficiency in the reduction of parameters analyzed, turbidity, pH, COD, BOD, TSS and TOC in relation to sulfate aluminum e polychloride aluminum, when comparing the physical and chemical characteristics of raw and treated effluent. Through the analysis it was found that the Fenton process has an efficiency on average of 92% of turbidity and 94% of COD and 90,5% of BOD, in reaction time of 60 minutes with agitation magnetic. The treated effluent presents values compatible for reuse.